Wanting and liking of Facebook functions and their correlation to problematic use - Dorottya Lakatos; Balázs Kovács; István Czigler; Zsolt Demetrovics; Domonkos File (Scientific Reports)
Abstract A key question about social media use is whether it constitutes an addiction. A possible frame of reference to investigate this question is the Incentive Sensitizations Theory (IST), as it provides a solid empirical background to understand the motivational and hedonic aspects of problematic behaviors. A central assumption of IST that addiction-related cues play a pivotal role in addictive behaviors has remained relatively understudied in the context of social media use. Given that social media platforms are multifaceted applications, the aim of this study was to explore motivational and hedonic responses associated with cues from different features of Facebook and their correlation with problematic use, analyzing survey data of 1436 respondents. The study primary focused on (1) the relationship between Facebook usage time/frequency, wanting and liking, and problematic use, and (2) the wanting and liking of 10 different Facebook notifications and their correlation to problematic use. Results aligned with predictions of IST, showing a positive correlation between wanting and usage time/frequency and problematic use, while marginal and inconsistent correlation was found with liking. Various Facebook functions contribute differently to its addictive potential, with social-communication features having the highest and general information features the lowest impact. In summary, the findings indicate that excessive Facebook use is primarily driven by compulsive tendencies rather than positive emotions. Although this study doesn’t conclusively determine if Facebook use can turn into an addiction, it appears that there are strikingly similar dynamics to substance use within the self-reported reflection of the motivational and hedonic systems.